Evaluating the environmental impacts of conventional and modular buildings in absolute measures: A case study across different geographical contexts. (September 2022) - Andersen, Sarah C.; Sohn, Joshua; Oldfield, Philip; Birkved, Morten
Abstract: This paper assesses the environmental impacts of conventional and modular housing by applying measures of 'absolute environmental sustainability'. It seeks to determine 1) the environmental performance of typical housing across different geographic boundaries, in this case Australia and Denmark, to explore whether such buildings can be deemed to achieve absolute sustainability within the planetary boundaries, and how factors related to location impact this, and 2) whether modular buildings perform better in terms of absolute environmental sustainability. The research measures lifecycle environmental performance of four case study buildings (conventional and modular, in Australia and Denmark), across seven impact categories. Normalisation references are determined based on the carrying capacity of earth by allocating a percentage of its limited resources to housing. A building would be considered to achieve absolute environmental sustainability if its environmental burden is less than its allocated share of the carrying capacity. The results found that none of the four buildings met this criterion. The two Australian buildings exceeded their allocated capacity in six of the seven impact categories, with figures of 700–36, 000% above capacity. The two Danish buildings did so in five of the seven categories, with figures of 200–3700% above. Modular buildings generally had lower environmental impacts across all categories, but still exceeded their allocations. The primary contributor was the operational phase of the buildings' lifecycle. However, even when this was excluded, all four buildings' impacts remain above their allocated limits, suggesting that environmental reductions are necessary across both embodied and operational stages. Highlights: Environmental impacts of conventional and modular housing, applying measures of 'absolute environmental sustainability'. No studied case satisfied allocated absolute environmental sustainability measure across all included impact categories. Modular case study building designs perform better, relatively compared to the conventional counterpart. Comparison between countries helps highlight different issues in need of focus. Economic household or dwelling allocation performed should be further developed.